1993
DOI: 10.1128/mcb.13.2.970
|View full text |Cite
|
Sign up to set email alerts
|

Increased UV resistance of a xeroderma pigmentosum revertant cell line is correlated with selective repair of the transcribed strand of an expressed gene.

Abstract: A UV-resistant revertant (XP129) of a xeroderma pigmentosum group A cell line has been reported to be totally deficient in repair of cyclobutane pyrimidine dimers (CPDs) but proficient in repair of 6-4 photoproducts. This finding has been interpreted to mean that CPDs play no role in cell killing by UV. We have analyzed the fine structure of repair of CPDs in the dihydrofolate reductase gene in the revertant. In this essential, active gene, we observe that repair of the transcribed strand is as efficient as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…For example, cyclobutane pyrimidine dimers appear to be better tolerated in cellular genomes than (6-4) photoproducts, and cells can complete DNA replication with a large number of dimers still present (30,41). In addition, cyclobutane dimers are preferentially removed from transcribed genes (42). In the present analysis many complications of in vivo studies have been eliminated by comparing UV photoproducts in isolation under identical conditions.…”
Section: Gm2250mentioning
confidence: 80%
“…For example, cyclobutane pyrimidine dimers appear to be better tolerated in cellular genomes than (6-4) photoproducts, and cells can complete DNA replication with a large number of dimers still present (30,41). In addition, cyclobutane dimers are preferentially removed from transcribed genes (42). In the present analysis many complications of in vivo studies have been eliminated by comparing UV photoproducts in isolation under identical conditions.…”
Section: Gm2250mentioning
confidence: 80%
“…DNA repair is known to be heterogeneous, it has been found that active genes are often repaired more efficiently than inactive genes, (29)(30)(31) and that the transcribed strand is repaired more rapidly than the nontranscribed strand (27,32,33). These studies have mainly been performed with Southern blotting based methods which investigate damage at the level of the whole gene (10-20 kb).…”
Section: Discussionmentioning
confidence: 99%
“…This mutation appears to reduce the capacity for repair of cyclobutane dimers specifically in inactive regions of chromatin (14,15). We wanted to investigate the intracellular function of XPA by development of an inducible gene expression system with which variations of XPA expression could be related to DNA repair and cell survival.…”
Section: Control Of Dna Repairmentioning
confidence: 99%